SKRINING PENGGUNAAN HAND SANITIZER KOMERSIAL DENGAN DAN TANPA KANDUNGAN EKSTRAK DAUN SIRIH TERHADAP JUMLAH KUMAN PADA TELAPAK TANGAN - Evy Ratnasari Ekawati; Dheasy Herawati; Ayu Susanti (Jurnal SainHealth, 2021)
The hands are one of the media for spreading pathogenic germs, which by washing hands are expected to reduce or kill these germs.  Under certain conditions, running water sources and soap are not available.  Hand sanitizer is an antiseptic that is used to clean the hands if no water and soap are found. The content of substances that are antiseptic, such as betel leaf extract in hand sanitizer is reported to reduce the number of germs. The goal of the study was to compare the total number of germs on the palms after using a commercial hand sanitizer that contained and did not contain betel leaf extract. This type of research uses comparative analytical observational studies using a cross-sectional approach.  The sample used in this study was as many as 18 health workers at LabKesDa Surabaya who used commercial hand sanitizer products with and without betel leaf extract. Supporting data on the study was a questionnaire given to respondents. The results of the swab of the palm and between the fingers of the respondents after using the hand sanitizer were tested by Mann Whitney and obtained a significance value of 0.000 < a= 0.05, meaning that there is a difference in the total number of germs on the palm and between fingers that use hand sanitizer with and without betel leaf extract. The use of a commercial hand sanitizer with betel leaf extract is more effective in lowering the totalnumber of germs on the palm and between the fingersKeywords : Commercial hand sanitizer, betel leaf extract, total number of germs, palms